2020
DOI: 10.1101/2020.07.03.185843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BAZ2A association with H3K14ac is required for the transition of prostate cancer cells into a cancer stem-like state

Abstract: AbstractProstate cancer (PCa) is one of the most prevalent cancers in men. Cancer stem cells are thought to be associated with PCa relapse and represent a target against metastatic PCa. Here we show that BAZ2A (also known as TIP5), a factor previously implicated in aggressive PCa, is required for the dedifferentiation of PCa cells into a cancer stem-like state. We found that BAZ2A genomic occupancy in PCa cells coincides with H3K14ac enriched chromatin regions. This association… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…These results indicate that the interaction with these target loci is not mediated by BAZ2A-TAM domain. Further, they support previous data showing that it is the BAZ2A-BRD domain to be required for the interaction of these regions that are enriched in H3K14ac (Peña-Hernández et al, 2021). Consistent with previous results (Mayer et al, 2006), the ChIP analysis showed that the interaction of BAZ2AΔTAM with the promoter of rRNA genes was reduced compared to BAZ2AWT (Fig.…”
Section: Baz2a Regulates a Set Of Genes Involved In Pca Through Its Tam Domainsupporting
confidence: 92%
See 4 more Smart Citations
“…These results indicate that the interaction with these target loci is not mediated by BAZ2A-TAM domain. Further, they support previous data showing that it is the BAZ2A-BRD domain to be required for the interaction of these regions that are enriched in H3K14ac (Peña-Hernández et al, 2021). Consistent with previous results (Mayer et al, 2006), the ChIP analysis showed that the interaction of BAZ2AΔTAM with the promoter of rRNA genes was reduced compared to BAZ2AWT (Fig.…”
Section: Baz2a Regulates a Set Of Genes Involved In Pca Through Its Tam Domainsupporting
confidence: 92%
“…KDM1A inhibitors upregulated the expression of genes linked to inactive BAZ2A-bound C2enhancers that are characterized by low H3K4me1 and H3K27ac levels (Peña-Hernández et al, 2021). KDM1A is highly expressed in various human malignancies and its activities were linked to carcinogenesis, making it a possible target for anticancer treatments (Maiques-Diaz and Somervaille, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations